2011
DOI: 10.1177/0098628311421327
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook to Connect Alumni, Current Students, and Faculty

Abstract: Maintaining contact with alumni can result in a number of benefits for psychology departments. For example, alumni may give feedback useful for curriculum assessment and departmental planning, assist with recruiting, and provide current students with information about jobs and graduate school. The authors describe a Facebook group they created for their department to connect alumni, current students, and faculty. A year later, members evaluated the site. Respondents agreed that it was a valuable resource, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…This view is supported by the result reported in related literature that courses involving cooperative learning contribute to learning (Al-Rahmi & Othman, 2013;Biasutti, 2011;Ekici & Kiyici, 2012;Forkosh-Baruch & Hershkovitz, 2012;Grosseck et al, 2011;Hung & Yuen, 2010;R. Junco et al, 2011;Kabilan et al, 2010;Lawson et al, 2011;Mazer et al, 2007Mazer et al, , 2009Wodzicki et al, 2012). Despite all these positive views, there were some other students with negative views who reported that it took quite a lot of time for them to carry out the activities involving cooperative learning.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 57%
“…This view is supported by the result reported in related literature that courses involving cooperative learning contribute to learning (Al-Rahmi & Othman, 2013;Biasutti, 2011;Ekici & Kiyici, 2012;Forkosh-Baruch & Hershkovitz, 2012;Grosseck et al, 2011;Hung & Yuen, 2010;R. Junco et al, 2011;Kabilan et al, 2010;Lawson et al, 2011;Mazer et al, 2007Mazer et al, , 2009Wodzicki et al, 2012). Despite all these positive views, there were some other students with negative views who reported that it took quite a lot of time for them to carry out the activities involving cooperative learning.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 57%
“…Much of the benefit of new technologies such as Computer Mediated Communication (CMC) and Web 2.0 tools is inherent in the increased opportunities for interaction and communication they provide for the learners (Conole & Dyke, 2004), but the use of new technologies alone cannot ensure learning without a strong pedagogical rationale and appropriate integration with the course (Kirkwood & Price, 2005). Activities that take place using new technologies need to be integrated (Biggs, 1999) with the rest of the course and not presented as optional; otherwise, learners might not give them much attention (Al-Rahmi & Othman, 2013;Ekici & Kiyici, 2012;Forkosh-Baruch & Hershkovitz, 2012;Grosseck, Bran, & Tiru, 2011;Hung & Yuen, 2010;Junco, Kabilan et al, 2010;Kirkwood, 2008;Lawson, Kleinholz, & Bodle, 2011;Mazer, Murphy, & Simonds, 2007Wodzicki, Schwämmlein, & Moskaliuk, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most important reason for the selection of Facebook is its popularity (Hargittai, ; Cain et al ., ; Madge et al ., ; Kabilan et al ., ; Wang et al ., ; Geyer, ). Other reasons include Facebook's functionality (Lawson et al ., ; Geyer, ), its suitability for collaborative activities (Lampe et al ., ), its facilitation of communication and interaction (Shih, ), students’ familiarity with it (Dabner, ), and its usability as an LMS (Wang et al ., ).…”
Section: Resultsmentioning
confidence: 99%